A compact design of MIMO patch antenna with high gain and symmetrical radiation pattern - Phuong Kim-Thi; Thang Nguyen-Van; Dat Nguyen-Tien; Tung Bui-Thanh (PLoS ONE, 2025)
This paper presents a compact design of multiple-input multiple-output (MIMO) microstrip patch antenna with high gain and symmetrical radiation pattern. The proposed antenna consists of dual-polarized crossed patches and T-junction power dividers. This combination makes the proposed design achieve high gain and high isolation with compact size and not requiring any additional decoupling structure. Especially, the use of dual-polarized patch can help to decrease the number of radiating elements while exhibiting high gain radiation. Besides, symmetrical radiation pattern in the broadside direction is also obtained. A prototype of 2-port MIMO antenna with overall dimensions of 0.72λ × 0.48λ × 0.04λ is fabricated and tested. The measured operating bandwidth is from 4.74 to 4.87 GHz. Across this band, high isolation of better than 20 dB can be obtained with small element spacing of 0.005λ. Besides, the measured far-field results observe symmetrical measured radiation pattern and broadside gain of 7.3 dBi. Further investigation also indicates that the proposed approach can be applied with large scale MIMO designs of 4 or 6 ports.